ANALISIS MANAJEMEN RISIKO PADA PROYEK PEMBANGUNAN GEDUNG LABORATORIUM TERPADU DAN PERPUSTAKAAN MAN 1 MALUKU TENGAH - Wally, Sinta Nuria; Jamlaay, Octovianus; Marantika, Meyke (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2022)
This study aims to determine the risks that occur in the Construction Project of the Integrated Laboratory Building and Man 1 Library, Central Maluku. The method used is a qualitative analysis method. The subjects in this study were workers in the Integrated Laboratory Building Development Project and the Man 1 Library in Central Maluku totaling 30 samples. The primary data collection techniques are through questionnaires and secondary data collection is through work items while the data analysis methods used are Validity Test, Reality Test, and data analysis with a risk matrix.